2014
DOI: 10.1111/1756-185x.12402
|View full text |Cite
|
Sign up to set email alerts
|

Pilot study assessing the novel use of musculoskeletal ultrasound in patients with rheumatoid arthritis to improve patient attitudes and adherence to medication

Abstract: Showing patients with RA 'real-time' US images of clinically inflamed joints resulted in a more favorable cost-benefit analysis, that is, increased patient belief in the necessity of medication versus concern about taking medication. There was no change in patient activation, medication adherence or disease severity.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 26 publications
(18 citation statements)
references
References 21 publications
0
18
0
Order By: Relevance
“…This should allow clinicians to allay patient concerns while highlighting treatment benefits [ 35 , 44 ]. Integrating MSKUS into an evidence-based educational framework may be beneficial because of its clinical value and as an educative tool to increase patient understanding of their disease [ 83 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This should allow clinicians to allay patient concerns while highlighting treatment benefits [ 35 , 44 ]. Integrating MSKUS into an evidence-based educational framework may be beneficial because of its clinical value and as an educative tool to increase patient understanding of their disease [ 83 , 86 ].…”
Section: Discussionmentioning
confidence: 99%
“…This type of disease visualisation, when combined with clinician-patient interaction at close quarters, may improve adaptation to the diagnosis, thereby increasing medication adherence and disease self-control. A recent study involving patients with active RA (DAS28 score > 2.6) found that showing RA patients “real-time” US images of their clinically inflamed joints resulted in a more favourable cost-benefit analysis as measured by the BMQ, that is, increased patient belief in the necessity of medication versus concern about taking medication [ 86 ]. However, this finding needs to be confirmed by larger, longer-term studies.…”
Section: The Use Of Musculoskeletal Ultrasonography As An Educatiomentioning
confidence: 99%
“…This is a complex issue and is impacted by patient knowledge and beliefs about their disease . There are few published data regarding the effect of musculoskeletal ultrasound on patient understanding and adherence to medication . This study suggests discussing DUS imaging results with patients may facilitate patient understanding and adherence to medication.…”
Section: Discussionmentioning
confidence: 86%
“…Showing patients with RA real‐time DUS images of their inflamed joints on one occasion increased their belief in the necessity of medication ( vs . concern about taking medication) . The visual nature of DUS may be important in patient education, as real‐time demonstration of joint structures and damage and the ability to highlight critical features for patients using their own anatomy may improve understanding and help patients recognize the need for medication …”
Section: Introductionmentioning
confidence: 99%
“…Real-time dynamic examination has made it possible to serve for a quick diagnostics purpose. MSUS performed by the physician also provides an excellent opportunity for patient education and to explain the rationale for treatments [7][8] . A study has also shown that the substitution of MSUS for magnetic resonance imaging of musculoskeletal disorders, when appropriate, would lead to large cost-savings for medicare 9 .…”
Section: Discussionmentioning
confidence: 99%